Perda de diversidade filogenética e alteração da estrutura filogenética em comunidades de aves em paisagens fragmentadas - Maure, Lucas Andrigo (2016)
Habitat loss and fragmentation are among the main threats of terrestrial tropical biodiversity. Understanding how these factors affect biodiversity has been a challenge for ecologists and conservationists. In this study, we tested the effect of forest loss and fragmentation in the phylogenetic diversity and in the phylogenetic structure in ecological bird communities along fragmentation gradient in Atlantic Forest. We evaluated bird communities in 83 forest fragments and described the surrounding landscapes with three indices: habitat amount, structural connectivity and patch aggregation. These metrics were calculated in 1 km buffers around the centroid of sampling fragment. Beside these landscape metrics, we also included elevation data as predictive or random variable, using linear and non-linear models. Our results showed that habitat amount and patch aggregation had strong effect in the phylogenetic diversity. However, this effect is conditioned by the elevation. Thus, the higher phylogenetic diversities were found in landscapes that simultaneously had higher values of habitat amount, patch aggregation and elevation. The increment of phylogenetic diversity with patch aggregation and habitat amount is mainly related with the increment of species richness in these landscape conditions. On the other hand, the elevation intereferences in phylogenetic diversity is probably related with climatic, evolutionary and biogeographic factors of the Atlantic Forest. We also found that structural connectivity interfered in the of phylogenetic structure pattern showing: clustered pattern in lower connectivity and dispersed pattern in higher connectivity. Thus, lower structural connectivity may act as environmental filter, selecting phylogenetically closely species.